Facile synthesis of N-acylbenzotriazoles from carboxylic acids mediated by 2,4,6-trichloro-1,3,5-triazine and triethylamine - Sirawit Wet-Osot (2018)
© 2015 Springer-Verlag Wien. Abstract A facile, efficient, and economic method toward N-acylbenzotriazoles was reported using 2,4,6-trichloro-1,3,5-triazine in combination with triethylamine as a carboxylic acid activator. Through reacting 1H-benzotriazole with the generated triacylated triazine intermediate, a series of N-acylbenzotriazoles could be rapidly prepared in high yields without column chromatography.